Assessment of free radical scavenging and digestive enzyme inhibitory activities of extract, fractions and isolated compounds from Tetracera macrophylla leaves - Opeyemi Roheem, Fatimah; Ahmed, Qamar Uddin; Mat So'ad, Siti Zaiton; Ali Shah, Syed Adnan; Latip, Jalifah; Alhassan, Alhassan Muhammad; Syed Mohammad, Sharifah Nurul Akilah (Elsevier GmbH, 2020)
Tetracera macrophylla is a valuable medicinal plant used traditionally for the treatment of various ailments. The crude ethanol extract was analyzed for its total phenolic and flavonoid contents. 2, 2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2′-azinobis-3-ethylbenzothiazine-6-sulfonic acid (ABTS) were used to examine the free radical scavenging capacity while enzyme inhibitory activity was assessed using α-amylase and α-glucosidase inhibitory methods. The crude extract was found to be rich in both phenolic and flavonoid contents (417.90 and5.86 μg GAE and QUE/mg dry weight, respectively) thus exhibited good radical scavenging activity on DPPH and ABTS radicals (IC50 values of 16.2 and 14.65 μg/mL, respectively). It also showed a promising concentration dependent enzymes inhibitory activity against α-amylase and α-glucosidase with IC50 of 72.17 and 76.16 μg/mL, respectively. Fractionation of active ethanol extract of T. macrophylla leaves through liquid-liquid partitioning yielded fractions Fa, Fb, Fc, and Fd. Among all the fractions, Fb (ethyl acetate fraction) showed the highest phenolic and flavonoid contents (206.34 μg/ GAE and 4.01 μg/ QUE respectively) and was also found to exhibit highest antioxidant and α-glucosidase inhibitory activities. The most active fraction, Fb upon purification yielded five compounds which were characterized and identified through different spectroscopic techniques. FTQ-4 among the compounds exhibited the strongest free radical and enzyme inhibitory activities followed by FTQ-3. All the compounds were isolated from this plant for the first time and found active against free radicals and/or digestive enzymes.These results further suggest the medicinal potential of T. macrophylla leaves as a therapeutic agent against hyperglycemia and free radical associated problems.